Second language comprehensibility and accentedness across oral proficiency levels: A comparison of two L1s. (August 2021) - Tergujeff, Elina
Abstract: Second language comprehensibility and accentedness are highly complex phenomena, and numerous studies have been conducted to better understand these constructs. However, research has seldom addressed L2 comprehensibility and accentedness in relation to speakers' proficiency in the target language. This study explores L2 English comprehensibility and accentedness across three proficiency levels. The speakers were 60 teenaged Finns, half of them speaking Finnish as their L1 and half speaking Finland-Swedish as their L1. Using 20-s speech samples, the comprehensibility and accentedness of the speakers were rated by 34 English-speaking teenagers on a 9-point scale. Comparisons were made regarding comprehensibility and accentedness between L1 Finnish and L1 Finland-Swedish speakers, and the data were also analysed for a possible relationship between the ratings and the speakers' overall oral proficiency in English. The results revealed a surprising difference between the language groups for speakers at proficiency levels B1–B2: Despite an equal proficiency assessment, L1 Finland-Swedish speakers were rated as more comprehensible and less accented than L1 Finnish speakers. Overall, the ratings were found to correlate with the speakers' oral proficiency, but the correlations were rather weak and the steps from one proficiency level to another often had only small effects on comprehensibility and accentedness.